UMPSA collaborates with KUTIP participants on IoT-Based Smart Agricultural System Project - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 27 June 2024 - The establishment of Pahang IoT Farmers Cooperative Berhad (KUTIP), an agricultural cooperative initiated by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) together with participants from the IoT-Based Smart Agricultural System Project, underscores the university's commitment to supporting small and medium enterprises (B40 group) in Pahang.